SPP PAYMENT SYSTEM ON SMU ADMINISTRATION USING VISUAL BASIC 6.0 KOSGORO - Elvina Tawa Beria Tondang; Aqwam Rosadi Kardian SKom, MM (Jurnal Sistem Informasi, 2004)
Writing contains administrative information on high school tuition payments KOSGORO Bogor, because there are no computer tools, the part that handles the administration of payments often have difficulty, among others: the duration record student data, administrative data are not neatly arranged, and others. Under these circumstances, the writer makes the system with reference to the current procedure. This system is expected to help overcome existing problems in order to improve efficiency, effectiveness and productivity and quality of schools.